Method for dispersion strengthening of FeCrAl-based alloy through nanometer ZrC
Through mechanical alloying and discharge plasma sintering technology of nano ZrC powder and FeCrAl pre-alloy powder, FeCrAl base alloy with excellent mechanical properties was prepared, which solved the problem of limited improvement in the mechanical properties of the existing FeCrAl base alloy and realized the Stable tensile strength and plasticity.
Patent Information
- Application Number
- CN202411423858.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
The yield strength and tensile strength of the existing FeCrAl-based alloys are limited to improve, making it difficult to meet the mechanical properties requirements under long-term exposure of high temperatures.
By mechanically alloying the nano ZrC powder and FeCrAl pre-alloy powder, and using discharge plasma sintering technology, the sintering temperature is controlled at 1000-1050°C to prepare a carbide diffusion reinforced alloy with excellent plasticity and tensile properties.
It significantly improves the yield strength and tensile strength of FeCrAl-based alloy, maintains the plasticity of the material, and maintains stable mechanical properties at high temperatures, and is suitable for nuclear fuel clad materials.
Smart Images

Figure CN119304179A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a method for nano ZrC dispersion strengthening FeCrAl-based alloy. Background Art
[0002] As the fourth generation nuclear reactor vessel cladding material, FeCrAl-based alloy has excellent anti-oxidation, anti-irradiation, and corrosion resistance as well as excellent mechanical properties. During service, stable nano-carbide dispersed phases (such as ZrC) can be added to the matrix. These particles can effectively pin dislocations, hinder dislocation movement and grain growth, thereby improving the service performance of FeCrAl-based alloys. As the core component of a nuclear power reactor, the performance of the fuel cladding directly determines the safety and reliability of the nuclear power reactor.
[0003] However, the yield strength and tensile strength of FeCrAl-based alloys prepared by existing technologies are limited, so it is necessary to provide a FeCrAl-based alloy with better yield strength and tensile strength. Summary of the invention
[0004] In order to solve the above technical problems, the present invention proposes a method for nano ZrC dispersion strengthening FeCrAl-based alloy. The present invention prepares a carbide dispersion strengthened alloy with good plasticity and excellent tensile properties by mechanical alloying and regulating the sintering temperature during spark plasma sintering. Moreover, the nano ZrC dispersion strengthened FeCrAl-based alloy of the present invention still has excellent tensile strength under high temperature and long-term exposure.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention:
[0007] A method for nano ZrC dispersion strengthening FeCrAl-based alloy, wherein nano ZrC powder and FeCrAl pre-alloyed powder are mixed to obtain mixed powder, the mixed powder is first subjected to mechanical alloying treatment, and then subjected to spark plasma sintering;
[0008] During spark plasma sintering, the sintering temperature is 1000-1050°C.
[0009] Preferably, during spark plasma sintering, the sintering temperature is 1000°C or 1050°C.
[0010] Preferably, the mechanical alloying process comprises the following steps:
[0011] The mixed powder is placed in a ball milling jar to remove oxygen and encapsulate, and the encapsulated ball milling jar is ball milled;
[0012] The ball milling is intermittent ball milling.
[0013] Preferably, the ball milling speed is 200-500 r / min.
[0014] Preferably, during ball milling, the ball-to-material ratio is 6:1.
[0015] Preferably, during ball milling, the grinding balls include large balls and small balls, both of which are 304 stainless steel grinding balls, the diameter of the large balls is 10 mm, the diameter of the small balls is 6 mm, and the ratio of the number of large balls to the number of small balls is 1:4.
[0016] Preferably, in intermittent ball milling, each ball milling is 40 minutes, and the rest time is 20 minutes, and the ball milling time is 30 hours (the 30 hours here refers to the ball milling time, excluding the rest time).
[0017] More preferably, the mechanical alloying treatment is:
[0018] The mixed powder is placed in a stainless steel ball mill for oxygen removal and packaging. This step is completed in a glove box, so that the ball mill is filled with high-purity Ar gas to ensure that the mechanical alloying process of the powder is carried out in an environment of high-purity Ar gas;
[0019] The encapsulated ball mill is fixed on a planetary ball mill for intermittent ball milling. The ball mill speed is 200-500r / min, the ball-to-material ratio is 6:1, the grinding balls include large balls and small balls, both of which are 304 stainless steel grinding balls, the diameter of the large ball is 10mm, the diameter of the small ball is 6mm, and the number ratio of large balls to small balls is 1:4. During intermittent ball milling, each ball milling is 40min, and the rest time is 20min, and the ball milling time is 30h. Too short ball milling time may lead to insufficient refinement of powder particles, while too long ball milling time may lead to excessive refinement of powder and excessive adhesion of particles, thereby affecting the plasticity of powder; in order to ensure the normal operation of the ball mill, prevent the mechanical alloying temperature from being too high, and ensure the ball milling efficiency, the ball mill program should be set to intermittent ball milling, stop the machine for a while after ball milling, and repeat the ball milling to make the reaction fully proceed.
[0020] Preferably, the mass ratio of the nano ZrC powder to the FeCrAl pre-alloyed powder is 0.5:99.5.
[0021] Preferably, during spark plasma sintering, the sintering pressure is 50 MPa, the holding time is 10 min, and the heating rate is 100° C. / min. During the sintering process, the powder particles are fully diffused to form a uniform and dense structure.
[0022] The present invention adds nano ZrC powder into the FeCrAl-based alloy, and prepares the carbide dispersion strengthened alloy (nano ZrC dispersion strengthened FeCrAl-based alloy) by mechanical alloying and spark plasma sintering. The alloy not only maintains the original plasticity of the material, but also significantly optimizes its yield strength and tensile strength. The tensile strength can reach 1058MPa, thereby improving the overall mechanical properties of the FeCrAl-based alloy. In addition, the alloy has stable mechanical properties under high temperature and long-term exposure environment, and is expected to be widely used in the engineering field.
[0023] The second technical solution of the present invention:
[0024] The present invention also provides a nano ZrC dispersion strengthened FeCrAl-based alloy prepared according to the above method, which has a yield strength of 851-915 MPa at room temperature and a tensile strength of 993-1058 MPa at room temperature. After aging for 2000 hours at a service temperature of 800°C, the alloy can still maintain a relatively high tensile strength, and as the aging time increases, the tensile strength maintains a stable state with a small change range, which proves that the nano ZrC dispersion strengthened FeCrAl-based alloy has good thermal stability and can be used to prepare nuclear fuel cladding materials.
[0025] The third technical solution of the present invention:
[0026] The invention also provides application of the nano ZrC dispersion strengthened FeCrAl-based alloy in preparing nuclear fuel cladding materials.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] In the technical solution of the present invention, during the ball milling process, the powder and the grinding balls collide at high speed, the ZrC powder and the FeCrAl pre-alloyed powder are fully mixed, and the ZrC nanoparticles pin dislocations, hindering the movement of dislocations and the growth of grains; the rapid heating and short holding time of spark plasma sintering greatly limit the abnormal growth of grains at high temperatures; the organizational stability of nano ZrC dispersion-strengthened FeCrAl-based alloys at high temperatures determines whether they can be safely used. ZrC usually exhibits good thermal stability at high temperatures, and high-temperature aging may cause the growth of dispersed phase particles, affecting the dispersion strength and reducing the strength and toughness of the alloy. The technical solution of the present invention significantly increases the mechanical properties of the material by mechanical alloying and spark plasma sintering in the form of dispersion strengthening and fine grain strengthening, while ensuring a certain plasticity. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0030] Figure 1 The SEM images of the nano ZrC dispersion-strengthened FeCrAl-based alloy matrix grains prepared in Example 1, Example 2 and Comparative Example 1, (a) is Comparative Example 1, (b) is Example 1, and (c) is Example 2;
[0031] Figure 2 The SEM images of the nano ZrC dispersion-strengthened FeCrAl-based alloy matrix grains and the dispersed distribution of ZrC in the matrix prepared in Examples 1 and 2, (a) is Example 1, and (b) is Example 2;
[0032] Figure 3 TEM images of the nano ZrC dispersion-strengthened FeCrAl-based alloy matrix grains and the dispersed distribution of ZrC in the matrix prepared in Examples 1 and 2, (a) is Example 1, and (b) is Example 2;
[0033] Figure 4 Schematic diagram of tensile specimens subjected to tensile tests for alloys prepared in Examples 1 to 7 and Comparative Examples 1 to 2, wherein R2 refers to a transition arc radius of 2 mm;
[0034] Figure 5 The stress-strain curves of the alloys prepared in Example 1-Example 2 and Comparative Example 1-Comparative Example 2 at room temperature;
[0035] Figure 6 These are stress-strain curves of the alloys prepared in Examples 2 to 7 and Comparative Example 2. DETAILED DESCRIPTION
[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0037] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0041] Unless otherwise specified, the room temperature and normal temperature in the present invention are both calculated as 25±2°C.
[0042] All raw materials used in the embodiments of the present invention are purchased from commercial sources. For example, FeCrAl pre-alloyed powder is purchased from AVIC Metallurgy Technology (Beijing) Co., Ltd.; ZrC powder is purchased from China Nuclear Power Research Institute.
[0043] The technical solution of the present invention is further illustrated by the following embodiments.
[0044] Example 1
[0045] In a glove box, weigh 99.5% FeCrAl pre-alloyed powder and 0.5% ZrC powder and place them in a ball mill. Then put 304 stainless steel grinding balls in a ratio of 1:4 for large and small balls and 6:1 for ball to material. The diameter of the large ball is 10 mm and the diameter of the small ball is 6 mm. The ball mill containing the mixed powder and grinding balls is sealed and filled with high-purity Ar gas to ensure that the mechanical alloying process of the powder is carried out in high-purity Ar gas. The mechanical alloying equipment uses a QM3SP4 planetary high-energy ball mill produced by Nanjing Nanda Instrument Factory. The speed is 300r / min, the ball milling time is 30 hours, and the ball milling mode is intermittent operation, with each ball milling for 40 minutes and a rest time of 20 minutes. The ball-milled powder was loaded into a graphite mold with a diameter of 20 mm, and the mold was placed in an SPS sintering furnace. To prevent the adhesion of the powder and the upper and lower punches caused by local overheating during the heating process, a piece of graphite paper was added between the upper and lower punches and the mold. Then the furnace chamber was vacuumed and the mold was pressurized with a pressure of 50 MPa. Finally, the temperature was raised to 1000°C at a heating rate of 100°C / min, and the temperature was kept at this temperature for 10 minutes, and then the furnace was cooled to obtain a nano-ZrC dispersion-strengthened FeCrAl-based alloy, which was recorded as 05ZrC-FeCrAl-based alloy.
[0046] Example 2
[0047] In the glove box, weigh 99.5% FeCrAl pre-alloyed powder and 0.5% ZrC powder and place them in a ball mill. Then put 304 stainless steel grinding balls in a ratio of 1:4 for large and small balls and 6:1 for ball-to-material ratio. The diameter of the large ball is 10 mm and the diameter of the small ball is 6 mm. The ball mill containing the mixed powder and grinding balls is sealed and filled with high-purity Ar gas to ensure that the mechanical alloying process of the powder is carried out in high-purity Ar gas. The mechanical alloying equipment uses the QM3SP4 planetary high-energy ball mill produced by Nanjing Nanda Instrument Factory. The speed is 300r / min, the ball milling time is 30 hours, and the ball milling mode is intermittent operation, with each ball milling for 40 minutes and a rest of 20 minutes. The ball-milled powder was loaded into a graphite mold with a diameter of 20 mm, and the mold was placed in an SPS sintering furnace. To prevent the adhesion of the powder and the upper and lower punches caused by local overheating during the heating process, a piece of graphite paper was added between the upper and lower punches and the mold. Then the furnace chamber was vacuumed and the mold was pressurized with a pressure of 50 MPa. Finally, the temperature was raised to 1050°C at a heating rate of 100°C / min, and the temperature was kept at this temperature for 10 minutes, and then the furnace was cooled to obtain a nano-ZrC dispersion-strengthened FeCrAl-based alloy, which was recorded as 05ZrC-FeCrAl-based alloy.
[0048] Example 3
[0049] The 05ZrC-FeCrAl-based alloy obtained in Example 2 was aged at 800°C for 50 hours.
[0050] Example 4
[0051] The 05ZrC-FeCrAl-based alloy obtained in Example 2 was aged at 800°C for 100 h.
[0052] Example 5
[0053] The 05ZrC-FeCrAl-based alloy obtained in Example 2 was aged at 800°C for 500h.
[0054] Example 6
[0055] The 05ZrC-FeCrAl-based alloy obtained in Example 2 was aged at 800°C for 1000 h.
[0056] Example 7
[0057] The 05ZrC-FeCrAl-based alloy obtained in Example 2 was aged at 800°C for 2000 h.
[0058] Comparative Example 1
[0059] Same as Example 2, except that the sintering temperature during spark plasma sintering is 950°C.
[0060] Comparative Example 2
[0061] The same as Example 2, except that no ZrC powder is added and the FeCrAl-based alloy is directly prepared.
[0062] The alloys prepared in the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 2 were subjected to sample processing to obtain tensile specimens that met the test requirements. The tensile performance test was carried out on a tensile machine (MetS Industrial Systems (China) Co., Ltd., model CMT5105). Under the test conditions, the temperature was room temperature and the tensile rate was 0.48 mm / min. In addition to the test, the polished samples were corroded and microstructures were observed and analyzed. SEM (produced by Hitachi, Japan, model S4800) and TEM (produced by JEOL, Japan, model JEM-2100f) were used for organizational characterization.
[0063] The SEM images of the nano ZrC dispersion strengthened FeCrAl-based alloy matrix grains prepared in Example 1, Example 2 and Comparative Example 1 are shown in FIG. Figure 1 It can be observed that, comparing Example 1 with Example 2, there are a large number of defects on the substrate surface of Example 1, and a large number of holes lead to stress concentration, which affects the density of the material, reduces the tensile strength of the material, and makes the material brittle, increasing the risk of its fracture.
[0064] The SEM images of the nano ZrC dispersion-strengthened FeCrAl-based alloy matrix grains and the ZrC dispersion distribution in the matrix prepared in Example 1 and Example 2 are shown in FIG. Figure 2 It can be seen that the alloy grains prepared in Example 1 and Example 2 are of different sizes. With the increase of sintering temperature, the grain size also increases, but the magnitude of size growth is not very large. This is because the added nano ZrC particles are pinned at the grain boundaries, hindering the migration of grain boundaries, and playing a good role in inhibiting the grain growth caused by high temperature during the sintering process. Figure 2 It is observed in (a) and (b) that ZrC is densely distributed at the grain boundaries and inside the grains.
[0065] The TEM microstructures of Example 1 and Example 2 are as follows: Figure 3 As shown, the matrix of both is composed of large grains and small grains, and ZrC particles with sizes of several nanometers and tens of nanometers are observed inside the grains. These nanocarbide particles are densely distributed and can effectively hinder dislocation movement and inhibit grain growth, thereby improving the overall performance.
[0066] The tensile strength of the alloys prepared in Examples 1 to 7 and Comparative Examples 1 to 2 was tested, wherein the schematic diagram of the tensile specimen is as follows: Figure 4 The stress-strain curve is shown in Figure 5 and Figure 6 The results are listed in Table 1.
[0067] Table 1
[0068]
[0069] from Figure 5 and Figure 6As can be seen from the data in Table 1, after the carbide dispersed phase is added to the pre-alloyed powder for mechanical alloying, the sample sintered at a suitable spark plasma sintering temperature can improve the material density and the mechanical properties of the material. The analysis of the tensile strength and plastic deformation results of Example 1-Example 2 and Comparative Example 1-Comparative Example 2 shows that the tensile strength of the 05ZrC-FeCrAl-based alloy prepared by mechanical alloying and spark plasma sintering by adding nano ZrC powder to the FeCrAl pre-alloyed powder has been significantly improved while maintaining a certain plasticity. The tensile strength of Example 1 is 287MPa higher than that of Comparative Example 2, an increase of 37.2% year-on-year, and the tensile strength of Example 2 is 222MPa higher than that of Comparative Example 2, an increase of 28.8% year-on-year. The performance test results of Example 1, Example 2 and Comparative Example 2 show that the addition of nanocarbides can effectively pin dislocations, hinder dislocation movement, and improve organizational properties. During the sintering process, the nano ZrC particles did not react significantly with the matrix, and were always dispersed in the form of ZrC at the grain boundaries and inside the grains throughout the entire process; the increase in sintering temperature promoted grain growth to a certain extent. Compared with Example 1, Example 2 had a 1.7% increase in plasticity and a 6.5% decrease in tensile strength. Although the changes in plasticity and tensile strength were not obvious enough, they were also affected by fine grain strengthening. Under the combined effect of fine grain strengthening and nano carbides, the overall mechanical properties of the material were improved.
[0070] The analysis of the tensile strength and plastic deformation results of Examples 3 to 7 above shows that, compared with Comparative Example 2 in which no ZrC powder is added, the products after high-temperature aging can still maintain a relatively high tensile strength, and as the aging time increases, the tensile strength of the samples maintains a stable state with little change, which indicates that the strengthening effect of ZrC does not significantly decay during the high-temperature aging process, and the thermal stability of the carbide ensures the thermal stability of the 05ZrC-FeCrAl-based alloy.
[0071] In summary, in the present invention, by adding nano ZrC powder, adopting the preparation method of mechanical alloying and spark plasma sintering, the second phase particles are dispersed in the matrix, and a 05ZrC-FeCrAl-based alloy with high density and excellent mechanical properties is obtained. Through the study and mechanical property test of the 05ZrC-FeCrAl-based alloy prepared by the present invention, it can be obtained that the incorporation of nano ZrC powder enables the FeCrAl-based alloy to maintain excellent plasticity while improving the tensile strength. The sintering temperature has a certain influence on the matrix grains and organization. The appropriate sintering temperature can not only improve the matrix density, but also improve the overall mechanical properties. At high temperatures, the thermal stability of the nano ZrC particles ensures the thermal stability of the 05ZrC-FeCrAl-based alloy, so that it still has excellent tensile strength under long-term exposure to high temperatures.
[0072] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for nano ZrC dispersion strengthening of FeCrAl-based alloy, characterized in that: After mixing the nano ZrC powder and the FeCrAl pre-alloyed powder, a mixed powder is obtained, the mixed powder is first subjected to a mechanical alloying treatment, and then subjected to spark plasma sintering; During spark plasma sintering, the sintering temperature is 1000-1050°C.
2. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 1, characterized in that: During spark plasma sintering, the sintering temperature is 1000°C or 1050°C.
3. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 1, characterized in that: The mechanical alloying process comprises the following steps: The mixed powder is placed in a ball milling jar to remove oxygen and encapsulate, and the encapsulated ball milling jar is ball milled; The ball milling is intermittent ball milling.
4. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 3, characterized in that: The ball mill speed is 200-500r / min.
5. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 3, characterized in that: During ball milling, the ball-to-material ratio is 6:
1.
6. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 3, characterized in that: In intermittent ball milling, each ball milling time is 40 minutes, and then rest for 20 minutes, and the total ball milling time is 30 hours.
7. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 1, characterized in that: The mass ratio of the nano ZrC powder to the FeCrAl pre-alloyed powder is 0.5:99.
5.
8. The method for nano ZrC dispersion strengthening of FeCrAl-based alloy according to claim 1, characterized in that: During spark plasma sintering, the sintering pressure is 50 MPa, the holding time is 10 min, and the heating rate is 100 °C / min.
9. A nano ZrC dispersion strengthened FeCrAl based alloy, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the nano ZrC dispersion strengthened FeCrAl based alloy according to claim 9 in the preparation of nuclear fuel cladding materials.
Citation Information
Patent Citations
Preparation method of nano ZrC reinforced FeCrAl alloy
CN109794613A
Dispersion strengthened FeCrAl alloy material
CN111809119A
High-strength FeCrAl-based alloy
CN113278895A
ZrC reinforced FeCrAl alloy and preparation method thereof
CN115852230A
High-toughness ultra-fine grain layered FeCrAl-based alloy material and preparation method thereof
CN118360554A